The Post-Romantic Predicament. - De Man, Paul (Frontiers of theory., 2012)
A collection of critical texts from Paul de Man's Harvard University years, published for the first time. These essays, brought together from the Paul de Man papers at the University of California (Irvine), make a significant contribution to the cultural history of deconstruction and the present state of literary theory. From 1955 to 1961, Paul de Man was Junior Fellow at Harvard University where he wrote a doctoral thesis entitled 'The Post-Romantic Predicament: a study in the poetry of MallarmÃ♭ and Yeats'. This dissertation is presented alongside his other texts from this period, including essays on HÜlderlin, Keats and Stefan George. This collection reflects familiar concerns for de Man: the figurative dimension of language, the borders between philosophy and literature, the ideological obfuscations of Romanticism, and the difficulties of the North American heritage of New Criticism. Key Features. The first collection of texts by Paul de Man published since the posthumous Aesthetic Ideology (1997) The missing link in the published de Man corpus Showcases important contributions to the analysis of Romantic and Post-Romantic poetry that engaged de Man for most of his life